Quantification of seed–soil contact of sugar beet (Beta vulgaris) using X-ray Computed Tomography - Blunk, Sebastian; Malik, Ali Hafeez; de Heer, Martine I.; Ekblad, Tobias; Bussell, Jennifer S.; Sparkes, Debbie L.; Fredlund, Kenneth; Sturrock, Craig J.; Mooney, Sacha J. (BioMed Central, 2017)
Abstract Background: Seed–soil contact is important to ensure successful germination, however, there is a paucity of reported studies that have quantified the microstructure at and around this critical interface, mainly due to the opacity of soil. Results: Here we describe a novel methodology to non-destructively calculate the seed–soil contact area using X-ray Computed Tomography. Under controlled conditions, we observed that seed–soil contact was strongly influenced by the size and type of seed, with a seed–soil contact of ca. 15% for naked sugar beet seeds compared to ca. 32% for pelleted and coated seeds. Similar results were obtained for seeds sampled from the field albeit with a higher spatial variability. Conclusions: By application of this new quantification method it is hoped seed enhancement technologies can be optimised and ultimately seedbed preparation improved to ensure better germination.